PENGARUH LAPISAN CHROMIUM PADA LOGAM BESI DENGAN PROSES ELECTROPLATING DALAM KETAHANAN TERHADAP KOROSI - Feriansah, Arif; Achmad, Ali (Universitas Muhammadiyah Pekajangan Pekalongan, 2018)
Abstraction Influence of chromium in ferro with electroplating process using chromium for layer metal iron assisted positive eletric current and negative current in chemistry fluid. Automotif industry usually apply for out layer automotif component to hamper corrosion. Researching at augustus until september 2016 in technic enginering laboratory politeknik muhammadiyah pekalongan with chromic acid and sulfuric acid 500 gram and 5 gram and mix with 5 liter clear water. Iron metal received negative current and chromium received positive current electrik for 60 minute to layer three metal iron and next, testing concentration chromium layer in metal iron with spectrometer testing to knowing concentration before and after get corrosion and showing reduction concentration on 5V,8A down 3,21%, 6V,7A down 3,06%, and 6V,8A down 0,40% it?s proving that chromium have influence to holding corrosion before hit the metal iron. Keywords: iron, electroplating, corrosion.